Armed Conflicts and Its Impact on Human Rights - Mahmood, Mohammed Salman (Journal of Legal Sciences, 2017)
The United Nations (UN) has affirmed a corpus of international human rights of which the most significant legal formulation is the International Documents of Human Rights which encompasses the Universal Declaration of Human Rights (UDHR) 1948, etc. International lawyers consider the Universal Declaration to have the status of customary international law, establishing a common standard by which to judge states' actions to protect human rights from armed conflicts. The aim of this paper is to examine the impact of armed conflicts on civilian’s human rights. The methodology adopted in this paper is purely a library based research focusing mainly on primary and secondary sources. The paper concludes that a new Human Rights Council should be established to coordinate and organize the work of UN, also, the Human Rights Council could establish a framework that would enable these organizations to consolidate their efforts and prioritize human rights strategies for peace and development, as well as should be the Human Rights Council to establishment new international convention to protect human rights from armed conflicts.